ANALISIS EFEKTIVITAS PENERAPAN RENCANA KERJA DAN ANGGARAN TERHADAP REALISASI ANGGARAN PADA UNIT PENGEMBANGAN PRODUKTIVITAS DAERAH (UP2D) PROVINSI KALIMANTAN BARAT - B51109048, FIRDAUS (Jurnal Kajian Ilmiah Akuntansi Fakultas Ekonomi UNTAN (KIAFE), 2014)
This thesis entitled "Analysis of Implementation Effectiveness Against Work Plan and Budget Actual Budget on Unit Pengembangan Produktivitas Daerah (UP2D) Provinsi Kalimatan Barat, which discusses issues regarding the effectiveness of the application of the Work Plan and Budget of the budget that has been realized within a period of one year and what are the factors that lead to the realization of the effectiveness of the budget. The method used in this research is descriptive method of data collection techniques such as : interview, observation, and study of literature. Data analysis tool used is Calculation Effectiveness, a list of questions and analysis flowchart. From these results it is concluded that the mechanism of the process is the implementation of the budget on Unit Pengembangan Produktivitas Daerah (UP2D) Provinsi Kalimantan Barat has gone well and in accordance with the Regulation of the Minister of Home Affairs Number 13 of 2006, where indicated on the Process Work Plan and Budget as well as the amount of the budget that has been done effectively realized is above ? 75%. However, there still has not reached the realization that effective, where the rate is still below the actual budget of <75%. This shows that in fact there are several obstacles that led to the realization that the budget can not be fully realized effectively. Keyword : Application, Realization and Effectiveness